2001
DOI: 10.1006/viro.2001.1208
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Analysis of the Mandarin Fish Infectious Spleen and Kidney Necrosis Iridovirus

Abstract: The nucleotide sequence of the infectious spleen and kidney necrosis virus (ISKNV) genome was determined and found to comprise 111,362 bp with a G+C content of 54.78%. It contained 124 potential open reading frames (ORFs) with coding capacities ranging from 40 to 1208 amino acids. The analysis of the amino acid sequences deduced from the individual ORFs revealed that 35 of the 124 potential gene products of ISKNV show significant homology to functionally characterized proteins of other species. Some of the put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
181
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(190 citation statements)
references
References 64 publications
4
181
1
4
Order By: Relevance
“…Similar viruses have been described for a number of fishes including ALIV from African lampeye, GIV from grouper Epinephelus malabaricus, SBIV from sea bass , an RSIV-like iridovirus from striped beakperch Oplegnathus fasciatus (Jung & Oh 2000, Kim et al 2002, and ISKNV from the mandarinfish Siniperca chuatsi (He et al 2001). These viruses were proposed to form a separate taxonomic unit, and were collectively termed 'cell hypertrophy iridoviruses' (He et al 2001). Phylogenetic trees derived from major capsid proteins, cytosine DNA methyltransferase, ATPase, and DNA polymerase suggest that these viruses differ from other iridoviruses.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Similar viruses have been described for a number of fishes including ALIV from African lampeye, GIV from grouper Epinephelus malabaricus, SBIV from sea bass , an RSIV-like iridovirus from striped beakperch Oplegnathus fasciatus (Jung & Oh 2000, Kim et al 2002, and ISKNV from the mandarinfish Siniperca chuatsi (He et al 2001). These viruses were proposed to form a separate taxonomic unit, and were collectively termed 'cell hypertrophy iridoviruses' (He et al 2001). Phylogenetic trees derived from major capsid proteins, cytosine DNA methyltransferase, ATPase, and DNA polymerase suggest that these viruses differ from other iridoviruses.…”
Section: Discussionsupporting
confidence: 54%
“…Another grouper iridovirus, isolated from E. macabaricus (GIV, Miyata et al 1997) was reported in Thailand. This virus was closely related to RSIV and was molecularly clustered with other 'cell hypertrophy iridoviruses' (He et al 2001). ATPase gene-sequence analysis (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Especially in infectious virus diseases, a lot of pathogenic viruses were identified from freshwater and marine culture animals [103], and the complete genomes of several viruses, such as grass carp hemorrhage virus (GCHV) [104], shrimp white spot syndrome virus (WSSV) [105], mandarin fish infectious spleen and kidney necrosis iridovirus (ISKNV) [106], and flounder lymphocystis disease virus isolated in China (LCDV-C) [107], were sequenced in China. Moreover, their structure proteins were characterized [108][109][110][111], and some of them were functionally analyzed [112,113].…”
Section: Disease Resistance Trait and Candidate Disease Resistance-rementioning
confidence: 99%
“…Based on the Eighth Report of the International Committee on Taxonomy of Virus (ICTV), the family Iridoviridae has been subdivided into five genera: Iridovirus, Chloriridovirus, Ranavirus, Lymphocystisvirus, and Megalocytivirus [3]. To date, 12 genome sequences of iridoviruses including at least one from each genus have been completely sequenced and analysed [2,[4][5][6][7][8][9][10][11][12][13][14]. These analyses show that iridoviruses encode a number of cellular protein homologues that may be mostly involved in nucleic acid metabolism, such as ribonucleotide reductase (RR), thymidylate synthase (TS), deoxyuridine triphosphatase (DUT), and purine nucleoside phosphorylase (PNP) [15].…”
Section: Introductionmentioning
confidence: 99%